World Music Studio / Mohd Fakrul Razi Muhd Daud ... [et al.] - Muhd Daud, Mohd Fakrul Razi; Sejet, Irman; Darwin, Syafriandi; Ibrahim, Iswansah; Saadun, Sahamir (Faculty of Civil Engineering, 2004)
The name for our company is "World Music Studio". It is generally believed that music can sooth our soul. When people play or listen to music, they tend to relax themselves. Therefore, we choose 'World Music' as our name to specify the importance of customer to us, as the music is importance to them.